2022
DOI: 10.3390/app12083772
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Estimation of Finger and Wrist Joint Angles Using a Muscle Synergy Based Musculoskeletal Model

Abstract: Recently, many muscle synergy-based human motion prediction models and algorithms have been proposed. In this study, the muscle synergies extracted from electromyography (EMG) data were used to construct a musculoskeletal model (MSM) to predict the joint angles of the wrist, thumb, index finger, and middle finger. EMG signals were analyzed using independent component analysis to reduce signal noise and task-irrelevant artifacts. The weights of each independent component (IC) were converted into a heat map rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…Using this research, future work will install the sEMG measurement and automatically control the motor with the calculated tension from sEMG signals. The missing muscle signals are proposed to be predicted from the remaining muscles using the muscle synergy methods [24][25][26][27]. In our previous works, we developed a method for estimating myoelectric signals and arm trajectories and forces in real time from electrocorticogram (ECoG) [28][29][30][31][32] and control of robotic arms using joint angles and myoelectric signals predicted by ECoG [33].…”
Section: Discussionmentioning
confidence: 99%
“…Using this research, future work will install the sEMG measurement and automatically control the motor with the calculated tension from sEMG signals. The missing muscle signals are proposed to be predicted from the remaining muscles using the muscle synergy methods [24][25][26][27]. In our previous works, we developed a method for estimating myoelectric signals and arm trajectories and forces in real time from electrocorticogram (ECoG) [28][29][30][31][32] and control of robotic arms using joint angles and myoelectric signals predicted by ECoG [33].…”
Section: Discussionmentioning
confidence: 99%
“…For Task 1, participants needed to wear Perception Neuron glove, the measured angles, raw sEMG signals, estimated joint angle and the system outputs were acquired via LSL for evaluation. Since this was a regression prediction task, we chose Pearson correlation coefficient (CC) (Taylor, 1990 ; Stapornchaisit et al, 2019 ; Qin et al, 2021 ; He et al, 2022 ) as the metric to evaluate the prediction accuracy:…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the MSK model built on MS features and MU neural features, study [41] suggested that the Synergistic Linear Regression Model (SLRM) based on Hierarchical Alternating Least Squares (HALS) and LR slightly surpassed traditional MSK approaches. Studies [42], [43] integrated MS features with MSK models, where [42] modeled MSs extracted through NMF-HP with L2 regularization constraint (NMF-HP-L2) into the GO-optimized Hill model, achieving superior predictive performance and stability over both Hill and NMF-Hill models. [43] constructed the MSK model using MSs extracted from independent components obtained via Adaptive Mixture Independent Component Analysis (AMICA) with NMF, resulting in better predictive performance than traditional MSK models, LR, and SVR.…”
Section: ) Hand-wrist Jointsmentioning
confidence: 99%